Understanding of generative art with python programming - Teddy Marius Soikun (Penerbit Universiti Malaysia Sabah, 2023)
The article uses the Python programming language to introduce generative arts as an alternative to conventional art and design. Understanding generative arts in the age of Artificial Intelligence (AI) is seen as a way forward to remain relevant. Through the use of a practice based research methodology, the article explores principles, processes, and tools for generating art through coding. Practical samples are used to demonstrate the potential of generative art through basic coding examples. This research also highlights the role of generative art in fostering interdisciplinary collaboration and transcending the boundaries of conventional art forms.